ANALISIS PENDAPATAN PEDAGANG KAKI LIMA DI JALAN JENDERAL SOEDIRMAN PURWOKERTO KABUPATEN BANYUMAS - Didit Suhartono (Universitas Amikom Purwokerto, 2010)
Purposes which wish reuched from this research are; a) knowing thetnfluence of education factor, work duration, number offamily, work time, and age torevenue of cloister merchan4 and b) to know faktor which have biggest elfect torevenue of cloister merchant. Pursuant to result of anova test (Flest), F value(counted) is 4,800. At 95 percent conf;dence level, table value ofF is 3,92. Thereby Fvalue (counteel) is more than it's tabel value, so H0 can be refused. It mean thatIogether [is] education (Xl), work duration (X2), number of fanily (X3), work time(X4), and age (X5) in together have signifcance efect to earnings (Y). Pursuant to ttest,tvalue(counted)forXl is2,8l8,lorX2is2,635,forX3is0,701,forX4isl,702,and for X5 is - 1 ,199. Table value of t at 95 percent confidence level is I ,980. T value(counted) for Xl and X2 are more than than it's table value (H0 can be refused). So,in individually education and year of service have an efect to earnings (Y). Then, tvalue (counted) X3, X4, and X5 are less than it's table value at 95 percentconfidence level (H0 accePT.ed). It's mean X3, X4, and X5 in individually has notsryntficance efect to revenue (I), From t-test also obtained constant and regressioncoefrcient from each independent variable. So, regression equation that can beformed is: Y: - 67468,7 + 24793,212 (XI) + 5782 (X2) + a020,662 (X3) +10165,732 (X1) - 1629,282 (X5). Pursuant to Fre obtained value of standardizedcoeficrent beta of Xl rs 0,373, X2 is 0,119, X3 is 0,087, X4 is 0,201, and X5 is -0,216. Thereby independent variable which own biggest value of standardizedcoeficient beta is X2 (0,119), It means independent variable that having biggestinfluence to reyenue (Y) is work duration.